Development of Interactive Digital Books Based on Rme to Improve Understanding Capability Concept of Fractions For Class V Students Elementary School - Haqiki Wulandari, Dessy; Amin Fauzi, Kms. Muhammad; Surya, Edy (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The aim of this research is to 1) determine the validity of interactive digital books based on realistic mathematics education on addition and subtraction of fractions; 2) find out the practicality of interactive digital books based on realistic mathematics education on addition and subtraction of fractions; and 3) determine the effectiveness of interactive digital books based on realistic mathematics education on adding and subtracting fractions. This research was conducted at SDN 054906 Tebasan Lama with research subjects namely class V students. This type of research is research and development with the Plomp model. The research instruments used were validation sheets, practitioner assessment questionnaires, student response questionnaires, and test instruments. The data collection techniques in this research are questionnaires and tests with data analysis techniques for testing validity, level of difficulty, discrimination and reliability for test instruments, as well as the N-Gain test. The results of this research show that 1) digital textbooks are valid, namely 98.1% (very valid) from material experts, 98.1% (very valid) from media experts, and 96% (very valid) from language experts; 2) practicality test results show that 16 out of 20 students gave very positive responses after using the product; and 3) digital books are declared effective from the analysis of learning outcomes, namely the average post-test score of students is greater than the average pre-test score, namely a score of 55 at the pre-test and a score of 88 at the post-test, classical completeness, namely in the pre-test only 15% of students completed, while in the post-test 100% of students were declared complete, and student activity, namely the final results, showed that the average percentage of student learning activity was 70% with good criteria.